Electron paramagnetic resonance tagged high-resolution excitation spectroscopy of NV-centers in 4H-SiC - Zargaleh, Soroush Abbasi (2019)
We show that electron paramagnetic resonance (EPR) tagged high resolution photoexcitation spectroscopy is a powerful method for the correlation of zero phonon photoluminescence spectra with atomic point defects. Applied to the case of NV centers in 4H-SiC it allows to associate the photoluminescence zero phonon lines (ZPL) at 1243, 1223, 1180, and 1176 nm with the (hk, kk, hh, kh) configurations of the NV−centers in this material. These results lead to a revision of a previous tentative assignment. Contrary to theoretical predictions, we find that the NV centers in 4H-SiC show a negligible Franck-Condon shift as their ZPL absorption lines are resonant with the ZPL emission lines. The high subnanometer energy resolution of this technique allows us further to resolve additional fine-structure of the ZPL lines of the axial NV centers which show a doublet structure with a splitting of 0.8 nm. Our results confirm that NV centers in 4H-SiC provide strong competitors for sensing and qubit application due to the shift of their optical transitions into the technology compatible near-infrared region and the superior material properties of SiC. Given that single center spin readout will be realized, they are suitable for scalable nanophotonic devices compatible with optical communication network.